THE EFFECT OF TRILOGY LEADERSHIP STYLE ON INNOVATION PERFORMANCE THROUGH DYNAMIC AMBIDEXTERITY CAPABILITY (DAC) MEDIATION (Study at the Youth Educational Center (YEC) Tutoring Institute) - Tomi Agus Triono; Ignatius Soni Kurniawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
This study aims to test whether dynamic ambidexterity capability mediates the relationship between trilogy leadership style and performance innovation. The study took samples in the business organization of a Youth Educational Center (YEC) tutoring institution located in the Wirobrajan area of Yogyakarta. The results showed that each component of the trilogy leadership style affected the dynamic ambidexterity capability variable and the performance innovations of its members. . The findings show that the trilogy leadership style can affect performance innovation directly or through mediating dynamic ambidexterity capability. This confirms that the dynamic ambidexterity capability is able to mediate the influence between the trilogy leadership style on innovation performance. Kata kunci : Ambidexterity, Leadership, Innovation